(untitled) (Journal of the College of Basic Education, 2023)
In this work we present the synthesis and spectroscopic determination of CuII, coordinate compound with the antibiotic metronidazole. An accurate method was chemically designated for the determination of metronidazole in pharmaceutical preparations. The green complex that was formed between copper(II) and metronidazole was studied in methanolic media. Coordination to metal ions is through its imidazolic nitrogen, while the hydroxyl and nitro groups act as supramolecular synthons. Pleated sheet or layers are formed by [Cu(metronidazole )2Cl(H2O)]Cl. The new analytical method based on measuring absorbance in UV-visible spectrum at λmax 400nm. Optimum pH and divalent copper ion concentration were estimated. Linearity(2×10-3-6×10-7), detection limit 6×10-7 M. were determined. The complex was identified with UV-visible and FT-IR spectra. The molar ratio also investigated and found 1:2(Cu: Metr).